Risk Management Strategies in Mining Operations with a Project Management Approach - hati, bunga (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This research explores risk management strategies in mining operations through a sustainability-based project management approach. The study emphasizes how integrating risk management practices, stakeholder engagement, and environmental impact assessment (EIA) within the project cycle can mitigate the environmental and social risks typically associated with mining activities. The methodological framework employed in the study is constructive, consisting of several stages: first, identifying key environmental and social risks; second, designing a comprehensive mitigation plan that applies project management techniques; third, implementing continuous monitoring supported by advanced sensor technology; and finally, evaluating the effectiveness of these strategies through before-and-after comparisons. The analysis of data from representative test sites reveals significant improvements in both environmental and social performance following the implementation of the mitigation strategies. Key findings include a reduction in pollutant levels (air, water, and soil) and CO₂ emissions across all test locations. Additionally, social indicators, such as the number of social complaints and unemployment rates, showed notable improvements. The study concludes that disciplined project management, when combined with real-time monitoring and effective stakeholder management, has the potential to significantly reduce water pollution levels by approximately 25%, while simultaneously enhancing the quality of relationships with local communities by about 15%. This improvement is attributed to more structured communication, participation, and empowerment programs, which foster stronger engagement with stakeholders and better social outcomes in mining operations.